LEGAL PROTECTION FOR NURSES AS HEALTH WORKERS WHO COMMIT MALPRACTICE CRIMES - Sry Ningsih Saragih; Muhammad Arif Sahlepi; Abdul Rahman Maulana Siregar (Journal of International Islamic Law, Human Right and Public Policy, 2024)
This study examines how legal protection for health workers nurses who commit malpractice in hospitals. Nurses are the most important human resources in hospitals because in addition to their dominant number reaching 55-65%, nurses are also a profession that provides constant and continuous services for 24 hours to patients every day. The nursing profession often comes into contact with legal problems, such as malpractice lawsuits as a result of errors and negligence made, or if the patient's expectations of the nurse do not match reality. So in providing health services, a nurse must comply with professional ethics (professional code of ethics) and also comply with applicable laws, regulations and legislation. This study aims to determine the legal regulations for nurses as health workers who commit malpractice and how their legal protection is. This study was conducted using a qualitative method with a normative juridical approach, examining laws, books, journals and articles that discuss the protection of health workers. The results of this study show that nurses as health workers carry out their health services as regulated in Law No. 17 of 2023 concerning Health and comply with Law No. 11 of 2020 concerning Job Creation and receive legal protection as stated in Law No. 17 of 2023 concerning Health, Article 3 (h), Article 12 (d), Article 193 and Article 273.